2021
DOI: 10.1088/1757-899x/1031/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

A SI engine performance parameters determination for gasoline and methane operation

Abstract: The present paper presents a study whose objective is to determine the performance parameters of an external mixture formation and spark-ignition engine when running on methane fuel. The experiments were carried out using optimum adjusting parameters for engine operation on methane and gasoline fuels. The parameters measured and determined are: brake specific fuel consumption, mean effective pressure, brake power, thermal efficiency, volumetric efficiency and etc. over the entire engine speed range. An analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The TD43F engine test rig uses an electrical dynamometer, which places a load on the engine and the power is dissipated in the resistor network. Therefore, brake power and brake torque are related by (equation 1) (Dimitrov et al, 2021), were simultaneously read from the meters, and shown for all types of fuel (B0, B10, B20, B40) on the (Figure 4). 4a and 4b) shown are the power and torque output of the test engine using different blends of biodiesel (B0, B10, B20, and B40).…”
Section: Evaluation Of Power Torque and Fuel Consumptionmentioning
confidence: 99%
See 4 more Smart Citations
“…The TD43F engine test rig uses an electrical dynamometer, which places a load on the engine and the power is dissipated in the resistor network. Therefore, brake power and brake torque are related by (equation 1) (Dimitrov et al, 2021), were simultaneously read from the meters, and shown for all types of fuel (B0, B10, B20, B40) on the (Figure 4). 4a and 4b) shown are the power and torque output of the test engine using different blends of biodiesel (B0, B10, B20, and B40).…”
Section: Evaluation Of Power Torque and Fuel Consumptionmentioning
confidence: 99%
“…Total fuel consumption (TFC) is the amount of fuel consumed by the engine per unit of time. Generally, it is expressed in Kg/h (Dimitrov et al, 2021).…”
Section: Measurement Of Fuel Consumptionmentioning
confidence: 99%
See 3 more Smart Citations